PENGEMBANGAN INSTRUMEN PROBLEM SOLVING DENGAN SAJIAN MASALAH MATEMATIKA KONTEKSTUAL DI SEKOLAH MENENGAH PERTAMA - Zulkarnain, Rezkie; Sugiatno, Sugiatno; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to produce problem solving instruments with appropriate contextual math problems in accordance with the needs of teachers and students in Junior High School. The method used in this research is the development method (R & D) with the model adapted from Sugiyono. The result of data analysis showed that: (1) the teacher positively stated that the teacher needed the problem solving instrument with a mathematical problem of contextual context which is feasible to be used in mathematics learning and 90% of the 20 students agreed if test problem solving with math problem good and worthy; (2) The problem solving instrument with a contextual mathematical problem is an instrument in the form of a written test that involves the process of problem solving and is made based on the context of the problems encountered in everyday life or related to the environment that can be observed or experienced by real research subjects as well as researchers; and (3) The developed instrument meets the criteria worthy means that the test instrument has valid indicator, realibel, has medium difficulty level, high distinguishing ability or minimum enough, and able to identify student ability in solving contextual mathematics problem according to each student's ability.Keywords : Problem Solving, Contextual Math ProblemsÂ